Differentiation of self and the decision to seek systemic psychotherapy: a comparison between a help-seeking and a normative sample. Issue 1 (2nd January 2021) - Lampis, J.; Cataudella, S.; Agus, M.; Carta, S.; Rodríguez-González, M.; Lasio, D.; Serri, F.; Galluzzo, W.
ABSTRACT: Bowen and colleagues argued through their clinical observations that psychological distress is a result of low levels of differentiation of self. Starting from these premises, the main objective of the present investigation was to compare a normative sample and a sample of adults seeking services at a systemic therapy clinic. Initially, we assessed differences between groups in dimensions related to differentiation of self and psychological distress. In the second step, we examined whether differentiation of self dimensions would increase or reduce the likelihood that an individual belonged to either of the two groups. The help-seeking sample was comprised of 64 adults seeking therapeutic services, and the normative sample was comprised of 85 students. All participants completed the Differentiation of Self Inventory and the Symptom Checklist-90-Revised. We found that the participants of the help-seeking sample had significantly higher scores on the Global Severity Index and in I-position and emotional cutoff dimensions. We also found that higher emotional cutoff was the strongest predictor of the probability of belonging to the help-seeking group in the hypothesized model. These data suggest that information about differentiation of self might enable counseling psychologists and therapist to define effective interventions.